Targeting protein kinase C-α prolongs survival and restores liver function in sepsis: Evidence from preclinical models - Ling Xiong; Dustin Beyer; Na Liu; Tina Lehmann; Sophie Neugebauer; Sascha Schaeuble; Oliver Sommerfeld; Philipp Ernst; Carl-Magnus Svensson; Sandor Nietzsche; Sebastian Scholl; Tony Bruns; et al. (Pharmacological Research)
Sepsis is a life-threatening organ failure resulting from a poorly regulated infection response. Organ dysfunction includes hepatic involvement, weakening the immune system due to excretory liver failure, and metabolic dysfunction, increasing the death risk. Although experimental studies correlated excretory liver functionality with immune performance and survival rates in sepsis, the proteins and pathways involved remain unclear. This study identified protein kinase C-α (PKCα) as a novel target for managing excretory liver function during sepsis. Using a preclinical murine sepsis model, we found that both PKCα knockout and the use of a PKCα-inhibitor midostaurin successfully restored liver function without hindering the host’s response or ability to clear the pathogen, highlighting PKCα’s vital role in excretory liver failure. In septic animals, both approaches significantly boosted survival rates. Midostaurin is the clinically approved active pharmaceutical ingredient in Rydapt, approved for the adjuvant treatment of FTL3-mutated AML. Here, it reduced plasma bile acids and related inflammation in those patients, opening a translational avenue for therapeutics in sepsis. Conclusively, our research underscores the significance of PKCα in controlling excretory liver function during inflammation. This suggests that targeting this protein could restore liver function without compromising the immune system, thereby decreasing sepsis mortality and supporting the recent paradigm that the liver is a hub for the host response to infection that might, in the future, result in novel host-directed therapies supporting the current state-of-the-art intensive care medicine in patients with sepsis-associated liver failure.